Rootstocks for 'Tahiti' lime - Stenzel Neusa Maria Colauto; Neves Carmen Silvia Vieira Janeiro (Scientia Agricola, 2004)
The 'Tahiti' lime (Citrus latifolia Tanaka) is an important commercial citrus cultivar in Brazil. 'Rangpur' lime has being used as its main rootstock, but it is susceptible to root rot caused by Phytophthora, reducing tree longevity. An experiment was set up in a randomized block design, with three trees per plot of each rootstock and four replicates, and run for 12 years, aiming to compare the performance of 'IAC-5 Tahiti' lime, budded on 'Rangpur' lime (Citrus limonia Osb.); 'C-13' citrange (Citrus sinensis (L.) Osb. × Poncirus trifoliata (L.) Raf.); 'African' rough lemon (Citrus jambhiri Lush.); 'Volkamer' lemon (Citrus volkameriana Ten. & Pasq.); trifoliate orange (Poncirus trifoliata (L.) Raf.); 'Sunki' mandarin (Citrus sunki Hort. ex Tan.) and 'Cleopatra' mandarin (Citrus reshni Hort. ex Tan.). Eleven years after the establishment of the orchard, trees with the greatest canopy development were budded on 'C-13' citrange and 'African' rough lemon, and both differed significantly from trees budded on trifoliate orange, 'Sunki' and 'Cleopatra' mandarins, which presented the smallest canopy development. Trees budded on 'Rangpur' lime and 'C-13' citrange had the highest cumulative yields, and were different from trees budded on trifoliate orange, 'Cleopatra' and 'Sunki' mandarins. There was no rootstock effect on mean fruit weight and on the total soluble solid/acid ratio in the juice. The 'Rangpur' lime and the 'Cleopatra' mandarin rootstocks reduced longevity of plants.